Tubal Twin Pregnancy Following IVF-ET: Case Report - Tunç Canda; Namık Demir; Orçun Sezer; Latife Doğanay (Medical Network, 2012)
We report a rare case of tubal twin pregnancy after in vitro fertilization and embryo transfer (IVF-ET) cycle at diagnosis before operation and two sacs were found to be located on the ovarian surface during laparoscopy. A 35-year old lady was admitted to the emergency unit with pelvic pain and was diagnosed with left tubal twin pregnancy with fetal cardiac activities 35 days after IVF-ET. Emergency laparoscopy was performed that showed the presence of two sacs were located on the left ovary, possibly, due to tubal abortion. Gestational sacs were extirpated by laparoscopy without damaging the ovary. Tubal twin ectopic pregnancy after IVF-ET is a rare condition that could be ended with tubal abortion and successfully managed conservatively by laparoscopic approach.